CYTOTOXICITY OF CHLOROFORM EXTRACT OF TODDALIA ASIATICA L. LEAF - Gopi Krishna, Sirimal; Sudarsanam, Gudivada; Penchala Pratap, Goli (International Journal of Ayurveda and Pharma Research, 2015)
The diverse and magnificent plant kingdom of the world is widely known for its medicinal importance. The potential medicinal properties of plant species have contributed significantly in the development of various herbal therapies for a number of diseases across the globe. The benefits of herbal medicine over allopathic medicine have helped medicinal plants to regain their importance in the field of health and medicine. Cancer is one of the major health problems that have widely affected the worlds population. There is a great need to combat this disease with better and more effective medication as compared to existing therapies. Toddalia asiatica belongs to Rutaceae, a woody liana, is used traditionally in the treatment of malaria, sprains, cough, fever, neuralgia, epilepsy, dyspepsia and other disease conditions. Extracts of the plant have been reported to have anticancer, anti-HIV, antimicrobial, antifeedant activities. In the present study an attempt has been made to investigate the cytotoxic effect of chloroform extracts of Toddalia asiatica leaves on cervical cancer cells. Extracts were studied for their toxicity by trypan blue dye exclusion assay, Cell viability was studied by LDH assay and Apoptosis was measured by DNA fragmentation assay. The study clearly showed the dose dependent cytotoxic effect of extract in HeLa cell line with an CTC50 of 170.00. The LDH leakage was observed in an dose dependent manner with an LDH IU/mg of total protein of 38.92.The dying cells showed characteristics of apoptosis such as, DNA fragmentation at both the concentrations that is at 100 and 200µg/ml. The data in the present study clearly demonstrated cytotoxic effects of extract on human cervical cancer cells.